(untitled) (Annals of Medical Research, 2021)
Aim: There is a requirement for a reliable serologic marker that can be used for the diagnosis of Irritable Bowel Syndrome (IBS). The aim of our study was to research whether serum levels of Alpha-galactosidase (AG) is associated with IBS and to assess quality of life (QOL) of IBS patients. Materials and Methods: 110 adult patients who were diagnosed with IBS were evaluated. 90 patients and 25 healthy volunteers were included. Patients were classified into subtypes: IBS-Diarrhea (IBS-D), IBS-Constipation (IBS-C), IBS-Mixed (IBS-M), and 30 patients were enrolled for each group. We administered the Short Form 36 (SF-36) to participants to evaluate QOL. Serum AG levels of participants was determined. Results: The mean AG levels of IBS-C and control group were significantly lower than the other groups (p<0.05). The SF-36 questionnaire scores, except for the vitality and mental health domains, were higher significantly in the control group compared to IBS patients (p<0.05). The mean scores of IBS subtypes were similar. In addition, the mean physical functioning score of the control group was higher in comparison with the IBS-D group significantly (p<0.05). Conclusion: Our study has shown that IBS impairs QOL in patients. In addition, we suggest that future studies needed for the role of AG deficiency in IBS patients.